Methods of intelligent control in LabVIEW programming - Lisowski, J.; Sokołowski, Ł. (Scientific Journal of Gdynia Maritime University, 2017)
The paper presents the principles and examples of the three most commonly used methods of intelligent control using the toolkit ICTL (Intelligent Control Toolkit for LabVIEW) – fuzzy controller FLC fuzzy logic, neuro-fuzzy regulator NF and genetic programming GA.